2020
DOI: 10.1111/jcmm.15724
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐specific protease 19 blunts pathological cardiac hypertrophy via inhibition of the TAK1‐dependent pathway

Abstract: Ubiquitin‐specific protease 19 (USP19) belongs to USP family and is involved in promoting skeletal muscle atrophy. Although USP19 is expressed in the heart, the role of USP19 in the heart disease remains unknown. The present study provides in vivo and in vitro data to reveal the role of USP19 in preventing pathological cardiac hypertrophy. We generated USP19‐knockout mice and isolated neonatal rat cardiomyocytes (NRCMs) that overexpressed or were deficient in USP19 to investigate the effect of USP19 on transve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Mounting evidence indicated that USP19 drives numerous cellular process. An important role for USP19 in the innate immune response has now been reported [ 22 ], with USP19 blunting pathological cardiac hypertrophy by inhibiting the inflammatory response [ 23 ]. Increasing literature indicated the correlation between USP family and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicated that USP19 drives numerous cellular process. An important role for USP19 in the innate immune response has now been reported [ 22 ], with USP19 blunting pathological cardiac hypertrophy by inhibiting the inflammatory response [ 23 ]. Increasing literature indicated the correlation between USP family and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the regulatory mechanism of DUBs in cardiac hypertrophy has the promise to provide a new therapeutic strategy. Previous research has already confirmed that the protein levels of USP10 (ubiquitin-specific peptidase 10), 21 USP18, 22 and USP19 23 were increased in mouse cardiac hypertrophy model induced by various factors, while USP2 24 and USP4 6 were consistently decreased in mouse hypertrophic hearts. These DUBs inhibit cardiac hypertrophy, reduce fibrosis levels, and improve cardiac function.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, USP19 is involved in regulation of cell cycle progression, DNA damage repair, apoptosis and autophagy (Lei et al, 2019;Miao et al, 2020). Here, we found that USP19 interacts with Nrf1 to enhance this CNC-bZIP stability and its transcriptional activity.…”
Section: Introductionmentioning
confidence: 66%